To eliminate police or redirect police funds? The impact of framing on public support for defunding the police - Smith, Olivia K. H.; Flick, Cassandra; Michalski, Nicholas D. (Frontiers in Psychology, 2024)
Objectives: Previous research and public polls demonstrate the public has varying levels of support for Defund the Police (DTP). However, much of these results assess how individuals feel about DTP rather than how they define it. Additionally, the literature fails to consider the role of these definitions and framing in individuals’ assessments of DTP. Using both qualitative and quantitative methodology, the current studies assess the following research questions: 1) How do individuals define DTP and to what extent do individuals support it? and 2) Does framing DTP as either redirecting police funds or eliminating police impact level of support? Method: Participants in both Study 1 (N = 93) and Study 2 (N = 494) were recruited from Amazon Mechanical Turk. Study 1 used a nonexperimental design, in which participants provided their definition of DTP and reported their level of support for DTP. Study 2 used a two-group experimental design in which participants were randomly assigned to one of two frames for DTP garnered from Study 1: redirect funds or eliminate police. Subsequently, participants reported their DTP support, DTP definition, familiarity with DTP, political orientation, and alignment with the frame presented. Results: In the absence of a frame, more participants opposed DTP than supported DTP. Participants also reported several different definitions of DTP, including decreasing police funds, redirecting police funds to social services, and eliminating police altogether. Notably, how an individual defined DTP was associated with support (e.g., defining DTP as redirecting funds was associated with greater support for DTP, compared to this theme being absent in participant definitions) . When using the redirect theme and eliminate theme as experimental frames (Study 2), a causal relationship was found between the framing manipulation and support of DTP (i.e., the redirect frame led to greater support than the eliminate theme). Conclusion: These findings shed light on how individuals conceptualize DTP, and most importantly, they provide evidence that differential framing can impact support for DTP in the general population. These results have implications for police reform advocates in that the words used to describe DTP can have an impact on public buy-in of policies.